Sarawak : quest for autonomy - Arnold, Puyok (Routledge, 2022)
Sarawak came undel the Brunei sultanate's rule in the early nineteenth century. The British adventr:rer Jan-res Brooke arrived in Kuchingr in 1839 to stop a local rebellion against the Brr-rnei sultanate. Blooke managed to thwart the rebellion and rvas installed as the rajah of Sararvak,2 starting the Brooke family\ reign over Sararvak for more than 100 years.